2016
DOI: 10.1371/journal.pone.0167036
|View full text |Cite|
|
Sign up to set email alerts
|

Should All Women with Polycystic Ovary Syndrome Be Screened for Metabolic Parameters?: A Hospital-Based Observational Study

Abstract: This hospital-based observational study aims to estimate differences in metabolic abnormalities between different polycystic ovary syndrome (PCOS) phenotypes and their distribution characteristics. The prevalence of metabolic abnormalities among different PCOS phenotypes, including diabetes mellitus (DM), metabolic syndrome (MS), pre-diabetes mellitus (pre-DM), insulin resistance (IR) and dyslipidemia were compared. A total of 2436 women who were ≥18 years old and who were hospitalized in Sun Yat-Sen Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
4
18
1
Order By: Relevance
“…In our study, the prevalence of insulin resistance in Brazil varied from 39.6% to 55.0%. It was lower than that of data from the US population (64%), 40 and higher than the prevalence in the Chinese population (28.5%–38.5%) 11 . However, it was similar to that obtained by the Italian (52.1%) and Indian (41%) studies 15,19 …”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…In our study, the prevalence of insulin resistance in Brazil varied from 39.6% to 55.0%. It was lower than that of data from the US population (64%), 40 and higher than the prevalence in the Chinese population (28.5%–38.5%) 11 . However, it was similar to that obtained by the Italian (52.1%) and Indian (41%) studies 15,19 …”
Section: Discussionsupporting
confidence: 42%
“…[41][42][43] In other population studies, the prevalence of low HDL-C varied from 29.3% to 97.3%, 11,[17][18][19] being lowest in the PCOS population in Argentina 18 and highest in the Indian PCOS population. 17 Regarding increased triglycerides, international data on triglycerides exhibited a prevalence of 9.6%-66.6% in women with PCOS, 11,[17][18][19] with Italian Hyperandrogenemia associated with increased sympathetic drive, previously described in PCOS, 44,45 contributed to an increased risk of hypertension in this syndrome. In accordance with this, previous studies have found that the prevalence of hypertension in PCOS ranges from 3.8% to 40.2%, 15,18,20,46 being higher in the presence of hyperandrogenism.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Women fulfilling the National Institute of Health (NIH) criteria for PCOS could have higher metabolic risk than patients with milder phenotypes (68) and metabolic disturbances were more pronounced in women with PCOS and hyperandrogenism as compared to women with no hyperandrogenism (69). However, high testosterone and PCOS phenotype did not predict glycemic status in three studies, two recent Nordic studies (3,11) and one Chinese study (70). It is important to recognize that BMI differed between different Rotterdam phenotypes (11).…”
Section: No Indication For Ogtt In All Women With Pcosmentioning
confidence: 96%